Clinical Evaluation of Terap C Vaccine in Combined Treatment with Interferon and Ribavirin in Patients with Hepatitis C - Dorta Guridi Zaily, MD, PhD, MS, PM; Castellanos Fernandez Marlen, MD, PhD, MS, PM; Dueñas-Carrera Santiago, PhD; Martínez Donato Gillian, PhD, MS; Valenzuela Silva Carmen, MS; Cinza Estevez Zurina, MD, MS; Arús Soler Enrique R., MD, PhD, PM; Alvarez-Lajonchere Liz, PhD; González Fabián Lisset, MD, MS; Lazo del Vallín Sacha, MD, MS; Ferrer Bataille Elena, LIC (Elsevier, 2017)
Background: An estimated 170 million individuals worldwide are infected with the hepatitis C virus (HCV). Although treatment options using a combination of pegylated interferon and ribavirin (P-IFN/RBV) are available, sustained clearance of the virus is only achieved in approximately 40% of individuals infected with HCV genotype 1. Recent advances in the treatment of HCV using directly acting antiviral agents have been achieved; however, treatment can be very expensive and is associated with substantial side effects. The development of a new treatment modality is needed. One possible modality could be specific immunotherapy. Terap C is a therapeutic vaccine candidate composed of pIDKE2, a plasmid expressing HCV structural antigens, with a recombinant HCV core protein, Co.120. Objective: To assess the safety and efficacy of concomitant therapy with the candidate vaccine, Terap C, IFN α-2b and ribavirin in untreated individuals with HCV genotype 1 infection. Methods: This was a Phase II randomized, placebo-controlled, double-blind clinical trial evaluating the safety and efficacy of Terap C concomitant with IFN α-2b/RBV in 92 treatment-naïve patients with HCV genotype 1 infection. The study was conducted at the Gastroenterology Institute in Havana, Cuba. Patients were randomly assigned to 1 of 5 groups. The control group (Group 1) received IFN α-2b/RBV and placebo for 48 weeks. Groups 2 and 3 were administered Terap C 6 and 9 times, respectively, in addition to standard IFN α-2b/RBV treatment. In groups 4 and 5, Terap C was introduced 12 weeks after the initiation of IFN α-2b/RBV and administered 6 and 9 times, respectively, concomitant with IFN α-2b/RBV. Results: All patients showed some adverse events. Out of 3615 adverse events, only 18.8% were considered to be probably associated with administration of Terap C. Most events (47.4%) were considered to be improbably associated with of administration Terap C. Only 33.8% were considered possibly temporarily associated with Terap C, and can be explained by the use of conventional IFN α-2b + RBV or by HCV itself. The most common adverse events (≥65%) observed were pain at the injection site, headache, asthenia, psychiatric disturbances, fever, and gastrointestinal symptoms. Regarding sustained virological response, a 20% superiority was observed in the patients who received concomitant Terap C treatments from the beginning of the study compared with those who started after Week 12. Conclusions: Vaccination with Terap C in patients with chronic HCV infection was safe and well tolerated. Clinical trial protocol code: IG/VHI/HC/0701; Public Register Code: RPCEC00000074.